The socio-psychological problems among Malay youth around flat housing in Kuala Lumpur: a case study - Omar Fauzee, Mohd Sofian; Tan, Choo Zen; Soh, Kim Geok; Mohseen, Hyder Salman (University Publications, 2010)
The purpose of this study is to investigate the socio-psychological problems among Malay youth around flat housing (low cost housing) in Kuala Lumpur. This qualitative study carried out interview on five Malay males as respondents aged 15-25 in four flat housing areas around Kuala Lumpur. The results from content analysis show that the factors that contribute to social problems in that area are the influence from the surrounding, low self-control and lack of attention from the parents. Factors that contribute to social problems include negative influence from friends, ignorant society and poverty while low self control is driven by a high negative desire and has no 'consciousness' to retreat from it. Parents fail to mould a happy family because of their ignorance to the needs of their children and too busy with daily work. The psychological applications concluded in the discussion and suggestion to overcome the social problems in the flat housing area is included for the purpose of further studies.